2017
DOI: 10.1002/adfm.201704420
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroinflammatory Response to Nanopatterning Parallel Grooves into the Surface Structure of Intracortical Microelectrodes

Abstract: The smooth surface structure of intracortical microelectrodes implanted within the nanometer‐scale architecture of brain tissue may contribute to the foreign body response. Here, the neuroinflammatory response to nanopatterning surface grooves etched directly on nonfunctional Michigan‐style microelectrodes is explored. Rats implanted with nanopatterned silicon microelectrodes are compared to smooth control implants to observe the effects the grooves have on neuroinflammation. Histology and real‐time PCR at 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 106 publications
0
72
0
Order By: Relevance
“…Bérces et al demonstrated that neural cells preferred binding to each other rather than the nanopatterned silicon and platinum MEA surfaces. Also, a study performed by Ereifej et al tested the effects of nanopatterned parallel grooves (200 nm wide and 200 nm deep with 300 nm spacing between) on MEA biocompatibility, specifically through determination of the overall inflammatory response. Results indicated that in comparison to the control, nonpatterned, MEA surfaces, the nanopatterned grooves did not significantly reduce neuroinflammation.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
See 1 more Smart Citation
“…Bérces et al demonstrated that neural cells preferred binding to each other rather than the nanopatterned silicon and platinum MEA surfaces. Also, a study performed by Ereifej et al tested the effects of nanopatterned parallel grooves (200 nm wide and 200 nm deep with 300 nm spacing between) on MEA biocompatibility, specifically through determination of the overall inflammatory response. Results indicated that in comparison to the control, nonpatterned, MEA surfaces, the nanopatterned grooves did not significantly reduce neuroinflammation.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…It is also possible that the material from which the MEA is fabricated could compromise the biocompatibility and performance of the MEA even after its topographical alterations. Materials utilized to fabricate MEAs in most of the aforementioned studies59a,74,76,77,79 were primarily very stiff materials, such as platinum, silicon, glass, and stainless metals. Given neuronal cells have considerable difficulty in attaching to stiff surfaces, it comes to no surprise that success is not always guaranteed when applying surface topography enhancements to stiff substrates.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…Surgical procedures were similar to our previously published methods [ 12 , 20 , 40 , 41 ]. Six male Sprague Dawley rats (8–10 weeks old, ~225 gm) were implanted with silicon, single shank, 16 channel intracortical microelectrodes (NeuroNexus A1x16-3mm-100-177-Z16, NeuroNexus, Ann Arbor, MI, USA) in the primary motor cortex (2mm lateral to midline and 2mm anterior to bregma) for eight weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was utilized to quantify the tissue reaction for activated microglia, astrocytes, blood–brain barrier permeability, and total neurons directly around the electrode implant site. Standard immunohistochemistry protocols used in our lab were conducted on the sliced brain tissue [ 40 , 41 , 45 ]. Briefly, two frozen slides per animal (each containing three tissue slices from layers III and V of the cortex) were equilibrated to room temperature (RT) for one hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation